2013
DOI: 10.1089/biores.2013.0008
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Neurite Outgrowth by Mechanical Cell Stretch

Abstract: Establishing extracellular milieus to stimulate neuronal regeneration is a critical need in neuronal tissue engineering. Many studies have used a soluble factor (such as nerve growth factor or retinoic acid [RA]), micropatterned substrate, and electrical stimulation to induce enhanced neurogenesis in neuronal precursor cells. However, little attention has been paid to mechanical stimulation because neuronal cells are not generally recognized as being mechanically functional, a characteristic of mechanoresponsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 22 publications
1
55
1
Order By: Relevance
“…Systems may be modified to provide additional device features, such as live-cell imaging, protein analysis, and higher throughput [98,[114][115][116][117]119]. Also of note are commercially available systems that use a vacuum to stretch the membrane (Flexcell International, Hillsborough, NC), which can be used for equiaxial strain studies [120][121][122]. Recently, Lau et al implemented a system using the Flexcell equiaxial device that was computer-controlled to generate arbitrary stretch waveforms based on physiologically relevant data [123].…”
Section: Multiaxial (Biaxial and Equiaxial) Stretch Methodsmentioning
confidence: 99%
“…Systems may be modified to provide additional device features, such as live-cell imaging, protein analysis, and higher throughput [98,[114][115][116][117]119]. Also of note are commercially available systems that use a vacuum to stretch the membrane (Flexcell International, Hillsborough, NC), which can be used for equiaxial strain studies [120][121][122]. Recently, Lau et al implemented a system using the Flexcell equiaxial device that was computer-controlled to generate arbitrary stretch waveforms based on physiologically relevant data [123].…”
Section: Multiaxial (Biaxial and Equiaxial) Stretch Methodsmentioning
confidence: 99%
“…70 Stretch also tended to increase the expression of neurofilament light chain (NFL), which is an important part of the neural cytoskeleton, but this change was not statistically significant. 70 This cyclic stretching is more relevant to skeletal muscle tissue than the axonal stretch growth, however, both studies demonstrate that carefully applied forces are able to improve outcomes for neuron cultures.…”
Section: Mechanical Stimulationmentioning
confidence: 98%
“…Other researchers have found that neurite outgrowth is increased by cyclic equibiaxial stretching. 70 Human neuroblastoma (SH-SY5Y) cells were cultured on BioFlex culture plates and mechanically stimulated to 10% at 0.25 Hz. 70 This culture was performed either with or without the addition of retinoic acid (RA), a well-known mediator of neurite outgrowth.…”
Section: Mechanical Stimulationmentioning
confidence: 99%
See 2 more Smart Citations